OpenAIRE guidelines for data archive, literature repository and CRIS managers - Príncipe, Pedro (2013)
Exposure and visibility of content from a range of European repositories will be significantly increased when a common and interoperable approach is taken and care to adhere to existing guidelines. This compatibility will lead to future interoperability between research infrastructures, and structured metadata is of benefit to individual data repositories and the knowledge community at large. OpenAIRE is starting to move from a publication infrastructure to a more comprehensive infrastructure that covers all types of scientific output. To put this into practice an integrated suite of guidelines were developed with specific requirements to support the goal of OpenAIRE and the European Commission. The poster will briefly outline the OpenAIRE Guidelines: Guidelines for Data Archive Managers, for Literature Repository Managers and for CRIS Managers. By implementing all three sets of the OpenAIRE Guidelines, repository managers will be able to enable authors who deposit publications in their repository to fulfill the EC Open Access requirements, as well as the requirements of other (national or international) funders with whom OpenAIRE cooperates. In addition it will allow the OpenAIRE infrastructure to add value-added services such as discoverability and linking, and creation of enhanced publications. In short, building the stepping-stones for a linked data infrastructure for research.